Assessment of Obstructive Sleep Apnea in Patients with Skeletal Class III malocclusion Following Mandibular Setback Surgery with Combination of STOP-BANG, Berlin, and Epworth Sleep Scale Questionnaires - Sahand Samiee rad; niusha yavari; fariba rezaitalab; majid eshghpour; Abdollah Javan; ali labafchi (Mashhad University of Medical Sciences, 2020)
Introduction: The present study aimed to evaluate the incidence of obstructive sleep apnea (OSA) after monomax mandibular setback surgery using a combination of Berlin, STOP-BANG, and Epworth SleepScale questionnaires. Materials and Methods: This double-blind quasi-experimental before-after study was carried out on a total of healthy patients with class III deformity and eligible for orthognathic mandibular setback surgery. Age, gender, body mass index, neck circumference, and amount of mandibular setback were recorded in the study checklist. The incidence of OSA was assessed for allthe patients 1 week before the operation and 1 and 6 months following the surgery using the aforementioned questionnaires under the supervision of a pulmonary specialist. Descriptive and analytical statistics were analyzed by SPSS software (version 17). A p-value of less than 0.05 was considered statistically significant. Results: A total of 30 patients, including 15 males and 15 females, with a mean age of 25.77±4.76 years participated in this study. The mean scores of OSA questionnaires increased a month after mandibular setback surgeryusing bilateral sagittal split osteotomy, compared to those reported before the operation; however, 6 months following the surgery, the results numerically reduced closer to the patient's normal condition. The amount of mandibular setback was directly correlated with the incidence of OSA in patients 1 and 6 months after the surgery based on all the three questionnaires; nevertheless, it was significantly and directly correlated with STOP-BANG questionnaire (p < /em><0.05). Conclusion: The obtained results of the present study indicated that there was no evidence of severe OSA 6 months following mandibular setback surgery. Additionally, obese patients and those submitted to a large amount of mandibular setback presented a higher chance of developing OSA. The findings of the present study showed that the results of the numerical changes of the sleep questionnaires and incidence of OSA 1 and 6 months after the surgery and before the operation were significantly lower in patients with mandibular setback up to 5 mm, compared to those with equal or greater than 5 mm.